Optimizing Base Shear Contributions in Steel-Braced RC Frames for Improved Seismic Performance - Birendra Kumar Bohara (Momentum International Journal of Civil Engineering (MIJCE), 2026)
This study investigates the seismic performance of reinforced concrete (RC) frames retrofitted with V-shaped steel bracing through a comparative analysis using Response Spectrum Analysis (RSA). A total of 24 models, 12 braced and 12 unbraced, were analyzed for 4-, 8-, 12-, and 16-story buildings, considering three base shear contributions (25%, 50%, and 75%) in columns observed. Key seismic parameters, including fundamental time period (FTP), top-story displacements, inter-story drift (ISD), base shear, and stiffness, were evaluated. Results demonstrate that V-bracing significantly improves seismic performance in low- to mid-rise buildings by reducing FTP (up to 76%), displacements (up to 72%), and ISD while increasing base shear demand (up to 59%) and structural stiffness. Higher base shear contributions in columns (e.g., 75%) led to increased displacements and reduced base shear, indicating a trade-off between column and bracing resistance. The findings highlight the effectiveness of steel bracing in retrofitting RC structures, with optimal performance observed when bracing resists a larger share of lateral forces. This study provides insights for seismic design and retrofitting strategies, emphasizing the role of dual systems in enhancing earthquake resilience. Further nonlinear analysis is recommended to explore post-yield behavior.